Adaptation to New Normal Conditions: Students Physics Learning Outcomes Using the Blended Learning Model - Dedi Riyan Rizaldi; Aris Doyan; Muh. Makhrus; Ziadatul Fatimah; Eris Nurhayati (International Journal of Asian Education, 2021)
Mataram City, West Nusa Tenggara Province, has started a transitional period, including in the world of education. The transition to the new normal requires adjusting the learning process to prepare students to learn normally. This study aims to describe students' physics learning outcomes using a blended learning model. This research is a type of experimental research. The research design was pre-experimental with the type of intact group comparison, where this type of research divided one class into two treatment groups. The population in this study were 11th-grade students of private madrasah majoring in science in Mataram city. The research sample was 50 students who were divided into two groups. The two groups were given a different treatment, where group 1 was taught with a blended learning model, while group 2 was taught using an online learning model. The physics learning outcome data were obtained through the initial and final tests, which were then analyzed descriptively using the N-gain test to determine the achievement of the learning process. Based on the research that has been done, it is found that the group taught with the blended learning model has a mean value of 70.14 with an N-gain of 0.36 (included in the medium category), which indicates that the use of blended models can be used to adjust students during a period of transition to a new normal.  The use of the blended learning model in the learning process is to accustom students to return to normal learning, namely face to face in madrasah. It was done to increase student motivation to learn during the COVID-19 pandemic.